2020
DOI: 10.3389/fpls.2019.01745
|View full text |Cite
|
Sign up to set email alerts
|

Lessons From 20 Years of Studies of Wheat Genotypes in Multiple Environments and Under Contrasting Production Systems

Abstract: Identifying opportunities and limitations for closing yield gaps is essential for setting right the efforts dedicated to improve germplasm and agronomic practices. This study analyses genotypes × environments interaction (G × E), genetic progress, and grain yield stability under contrasting production systems. For this, we analyzed datasets obtained from three Swiss trial-networks of winter wheat that were designed to evaluate genotypes under organic farming conditions, conventional management with low-inputs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…The concept of intensification has been used for both crop-specific and cropping systems (Andrade et al, 2017) approach. Similar to our research, other studies have evaluated management intensification strategies in wheat (Herrera et al, 2020;R.P. Lollato, Ruiz Diaz, et al, 2019;Mohamed et al, 1990;Quinn & Steinke, 2019;Roth et al, 2020;B.…”
Section: Impacts Of Agronomic Practices On Grain Yield and Uptake Of N P K And Ssupporting
confidence: 83%
See 1 more Smart Citation
“…The concept of intensification has been used for both crop-specific and cropping systems (Andrade et al, 2017) approach. Similar to our research, other studies have evaluated management intensification strategies in wheat (Herrera et al, 2020;R.P. Lollato, Ruiz Diaz, et al, 2019;Mohamed et al, 1990;Quinn & Steinke, 2019;Roth et al, 2020;B.…”
Section: Impacts Of Agronomic Practices On Grain Yield and Uptake Of N P K And Ssupporting
confidence: 83%
“…Russell et al, 2020). For example, Herrera et al (2020) evaluated genotypes and environments interaction and grain yield stability under different production systems such as organic F I G U R E 6 Shoot nutrient concentration of (a) N, (b) P, (c) K, and (d) S as affected by biomass during the growing season for standard (SM) and intensive (IM) management systems with (SM + Fung.) or without (IM-Fung.)…”
Section: Impacts Of Agronomic Practices On Grain Yield and Uptake Of N P K And Smentioning
confidence: 99%
“…Furthermore, when this latter work considered breadmaking cultivars only, no significant correlation was found in organic sites between cultivar age and grain yield either, whereas a significant breeding progress was found in non-organic sites. Similar conclusions were reached more recently in Central European environments by Herrera et al (2020) who, in addition, observed that the genetic effect on wheat yield trends over 20 years was significantly positive in 'conventional high-input' and 'conventional low-input' management system, but not significant in 'organic management'. Longer straw in historic cultivars can be associated with increased root proliferation (Bai et al 2013, Barraclough 2010, particularly in terms of seedling root growth (Wojciechowski et al 2009).…”
Section: Effect Of Cultivars On Crop Performance and Weed Abundancesupporting
confidence: 86%
“…Germplasm selection is an important consideration for farmers, as is the level of management intensity and inputs. A Swiss study examining 20 yr of winter wheat data shows that genetics explains more variation under a high‐input management approach than a low‐input or organic approach (Herrera et al., 2020), suggesting that high‐input management can optimize yields across varieties and enhance knowledge about variety yield potential. In Midwest states like Wisconsin, soft red winter wheat is commonly grown, which has higher yield potential than hard red winter wheat (Lollato, Roozeboom, Lingenfelser, Lemes da Silva, & Sassenrath, 2020), so additional inputs may be worthwhile if they lead to higher yields.…”
Section: Introductionmentioning
confidence: 99%